SEDIMENT PHOSPHORUS FRACTIONS AND PROFILE DISTRIBUTION AT DIFFERENT VEGETATION GROWTH ZONES IN A MACROPHYTE DOMINATED SHALLOW WULIANGSUHAI LAKE, CHINA - Liu Zh.; Jin Zh.; Li Ya.; Li T.; Gu J.; Gao S. (My University, 2007)
Sediment phosphorus (P) fractions and profile distribution at submerged macrophyte growth zone, emergent macrophyte growth zone and open-water zone were studied in Wuliangsuhai Lake, China, as well as the correlations among water content, grain size, and organic matter and P fractions. Among the three surveyed zones, the highest concentrations of most P forms occurred in the surface sediment and the lowest between a depth of 12 and 22 cm, except HCl-P and NaOH-P. Sediment phosphorus was mainly associated to inorganic forms (>50%) in three surveyed areas, and the highest value of inorganic phosphorus (IP) in the surface sediment was obtained from submerged macrophyte growth zone. Submerged and emergent macrophytes increased the IP content by 107 and 44 μg/g, respectively, in the surface sediment compared with open-water zone. Vertical profiles of IP in the three surveyed zones showed that the concentrations decreased from surface to 12 cm depth and then increased. There was a similar trend in the sediment profiles of organic phosphorus (OP) and total phosphorus (TP), but the highest concentration of OP and TP in surface sediment was obtained from the emergent macrophyte growth zone. Compared with open-water zone, the emergent macrophyte increased TP content in surface sediment by 1.73 times to 1,320 μg/g, while submerged macrophyte enhanced TP content in the surface sediment by 1.13 times to 865 μg/g. It was observed that in macrophyte growth zones, a strong linear correlation existed between organic matter and OP (r > 0.98), and the maximum concentrations of OP were present in the areas with maximum concentrations of organic matter. Results show that, although rooted macrophyte could uptake directly P from sediments, it is responsible for increasing the internal P loading especially OP by reducing current velocities, attenuating wave energy and generating organic residue in Wuliangsuhai Lake.
Keywords: PHOSPHORUS FRACTIONS; PROFILE DISTRIBUTION; EMERGENT MACROPHYTE; SUBMERGED MACROPHYTE; OPEN-WATER